Effect of sugars on post-thaw seminal characteristics of HF semen in tris bufferin absence and presence of glycerol - KUMAR, SATISH; SINGH, L P; MOHAN, GREESH; SAHNI, K L (The Indian Journal of Animal Sciences, 2013)
Post-thaw motility (PTM) and post-thaw aging motility (PTAM) were significantly (P <0.01) higher in tris containing glycerol than that without glycerol, almost with all the sugars. In the absence of glycerol post-thaw incubation motility(PTIM) and PTAM did not differ from each other due to different sugars. But in presence of glycerol PTM and PTIM were significantly (P< 0.01) higher with raffinose.than that with other sugars. Higher number of sperm survived freezing stress in presence of glycerol and per cent live sperm differed significantly (P< 0.05) due to different sugars. Glycerol and sugars combinedly exerted beneficial effect on acrosomal maintenance also. Higher number of per cent normal acrosome was recorded in presence of glycerol and sugars except 2.0% sucrose and 2.0% table sugar (the higher molecular weight sugars).